Core Values of Family Medicine in Europe: Current State and Challenges - Arvidsson, Eva; Švab, Igor; Klemenc-Ketiš, Zalika (Frontiers in Medicine, 2021)
Background Values are deeply held views that act as guiding beliefs for individuals and organizations. They state what is important in a profession. The aims of this study were to determine whether European countries have already developed (or are developing) documents on core values in family medicine; to gather the lists of core values already developed in countries; and to gather the opinions of participants on what the core family values in their countries are. Methods This was a mixed methods study, consisting of a quantitative and a qualitative part. The questionnaire was distributed as an e-survey via email to present and former members of the European Society for Quality and Safety in Family Practice (EQuiP), and other family medicine experts in Europe. The questionnaire included six items concerning core values in family medicine in the respondent’s country: the process of defining core values, present core values, the respondents’ suggestions for core values, and current challenges of core values. Results Core values in family medicine were defined or in a process of being defined in several European countries. The most common core values already defined were the doctor-patient relationship, continuity, comprehensiveness and holistic care, community orientation, and professionalism. Some countries expressed the need for an update of the current core values’ list. Most respondents felt the core values of their discipline were challenged in today’s world. The main values challenged were continuity, patient-centered care /the doctor-patient relationship and comprehensive and holistic care, but also prioritization, equity, and community orientation and cooperation. These were challenged by digital health, workload/lack of family physicians, fragmentation of care, interdisciplinary care, and societal trends and commercial interests. Conclusion We managed to identify suggestions for core values of family medicine at the European level. There is a clear need to adopt a definition of a value and tailor the discussion and actions on the family medicine core values accordingly. There is also a need to identify the core values of family medicine in European countries. This could strengthen the profession, promote its development and research, improve education, and help European countries to advocate for the profession.